PENINGKATAN HASIL BELAJAR KOGNITIF SAINS IPA FISIKA SISWA DENGAN MENERAPKAN MEDIA PERMAINAN TRUTH AND DARE - Mimmah, Mutham Mimmah; Nasir, Muhammad Nasir; ', Syahril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to determine improvement the learning outcomes cognitive science of physics by using the truth and dare game media. This research was conducted in SMPN 20 Pekanbaru precisely in Jebruari to June 2015. The subjects were students of class  VIII3 totaling 40 students consisting of 17 male students and 23 female students. Form the research is pre-experimental with One Group Pretest-Posttest Design. The instrument of data collection in this research is a cognitive achievement test consists of 20 multiple choice items. Analysis of the data in this research is a descriptive analysis and inferential analysis. Descriptive analysis of the results obtained from the absorption average of 41.50 students before treatment with unfavorable category, after being treated, absorption of 81.625 students with good category while the effectiveness of student learning before treatment have a category less effective after being treated, the effectiveness of learning effective category. It is also used inferential analysis through the sign test values ​​obtained Exact Sig. (2-tailed) = 0.000 <0.05 = 5% which means there is a significant increase. It can be concluded the use of truth and dare game media can improve the results of class VIII student of SMPN 20 Pekanbaru in the subject matter sounds. Keywords: Cognitive Learning Outcomes, Media Posters, Sounds